The efficacy and safety of CD7 chimeric antigen receptor T-cell therapy for hematologic malignancies: a systematic review and meta-analysis - Liu, Jile; An, Yuxin; Sun, Rui; Zhang, Xiaomei; Guo, Shujing; Gao, Xuejin; Zhao, Mingfeng (Frontiers in Oncology, 2025)
IntroductionCD7 chimeric antigen receptor T-cell (CAR-T cell) therapy is an emerging method for treating hematological malignancies, and is another breakthrough in CAR-T cell therapy.MethodsThis study summarizes the currently published clinical research results on CD7 CAR-T cells and evaluates the safety and effectiveness of CD7 CAR-T cell therapy.ResultsAmong the 13 studies included in this study, a total of 200 patients received CD7 CAR-T cell therapy, including 88 patients who received autologous CAR-T cells, 112 patients who received donor derived CAR-T cells. 87% (80% -94%, I2=29.65%) of patients achieved complete remission. The incidence of cytokine release syndrome (CRS) was 94% (88% -98%, I2 =32.71%, p=0.12), while the incidence of severe CRS (grade ≥ 3) was 12% (5% -20%, I2=41.04%, p=0.06). As for the incidence of immune effector cell-associated neurotoxicity syndrome (ICANS), it is 4% (1% -7%, I2=0, p=0.72). Through analysis of the key clinical issues, we found that consolidation allogeneic hematopoietic stem cell transplantation (allo-HSCT) after CAR-T cell therapy can significantly improve survival and avoid recurrence. Therefore, we believe that the consolidation allo-HSCT after CD7 CAR-T cell therapy should be advocated. And patients who received CD7 CAR-T cell therapy without gene editing had significantly longer overall survival than those who received CD7 CAR-T cell therapy with gene editing. This suggests that gene edited CD7 CAR-T cells may pose some potential risks that limit the long-term survival of patients.ConclusionOur study confirms the efficacy and safety of CD7 CAR-T cells and provides research directions for the subsequent treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=502896, identifier CRD42024502896.